2014
DOI: 10.1016/j.rmed.2013.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Asthma and allergic rhinitis increase respiratory symptoms in cold weather among young adults

Abstract: Our study shows that already in young adulthood those with asthma, and especially those with coexisting allergic rhinitis, experience substantially more cold temperature-related respiratory symptoms than healthy young adults. Hence, young adults with a respiratory disease form a susceptible group that needs special care and guidance for coping with cold weather.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 33 publications
2
31
1
2
Order By: Relevance
“…1623 completed questionnaires were received (response rate 64.0%). The respondents were a representative sample of the original baseline study population as reported in another study on the 20-year follow up [27]. The questionnaire contained several sections and was partly based on questions used in the previous follow-ups and research projects [28], [29].…”
Section: Methodsmentioning
confidence: 99%
“…1623 completed questionnaires were received (response rate 64.0%). The respondents were a representative sample of the original baseline study population as reported in another study on the 20-year follow up [27]. The questionnaire contained several sections and was partly based on questions used in the previous follow-ups and research projects [28], [29].…”
Section: Methodsmentioning
confidence: 99%
“…According to epidemiological surveys, a cold environmental stimulus is believed a ‘trigger’ exacerbating existing asthma symptoms, or may directly trigger asthma . Hyrkäs et al . surveyed 1623 young subjects and found that existing asthma increased the risks of all cold‐weather related respiratory symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Cold air induces respiratory inflammation in high-altitude region or in winter (Koskela 2007). especially in patients with respiratory disorders (Seys et al 2013;Hyrkäs et al 2014). At addition, reactive oxygen species are involved in physiological and pathophysiological processes in the lung (Al Ghouleh et al 2011).…”
Section: Resultsmentioning
confidence: 99%